IPV Screening and Readiness to Respond to IPV in Ob-Gyn Settings: A Patient-Physician Study - Katherine M. Jones; Laura H. Taouk; Neko M. Castleberry; Michele M. Carter; Jay Schulkin (Advances in Public Health)
Purpose. Intimate partner violence (IPV) is a serious, preventable public health concern that largely affects women of reproductive age. Obstetrician-gynecologists (ob-gyns) have a unique opportunity to identify and support women experiencing IPV to improve women’s health. Considering recent efforts to increase IPV awareness and intervention, the present study aimed to provide a current evaluation of nationally representative samples to assess ob-gyn readiness to respond to IPV as well as patient IPV-related experiences. Methods. 400 ob-gyns were randomly selected from American College of Obstetricians and Gynecologists’ (ACOG) Collaborative Ambulatory Research Network. Each physician was mailed one physician survey and 25 patient surveys. Results. IPV training/education and IPV screening practices were associated with most measures of ob-gyn readiness to respond to IPV. Among respondents, 36.8% endorsed screening all patients at annual exams; however, 36.8% felt they did not have sufficient training to assist individuals in addressing IPV. Workplace encouragement of IPV response was associated with training, screening, detection, preparation/knowledge, response practices, and resources. Thirty-one percent of patients indicated their ob-gyn had asked about possible IPV experiences during their medical visit. Conclusion. Findings highlight specific gaps in ob-gyns’ IPV knowledge and response practices to be further addressed by IPV training.